O processo de formação docente da pedagogia Waldorf: narrativas (auto)biográficas de professoras em formação. - Fernandes, Maria Martha Stussi (2017)
The present research leaned over at basics notions of Anthroposophy in the attempt to delve into the issues that brought to the surface the need to seek another look at education. The Waldorf Pedagogy emerged from a local need in Stuttgart, Germany, in 1919 and has been multiplying exponentially these days around the globe. Teacher’s training within this pedagogy takes the form of seminars over three to four and a half years. This study sought through the (auto)biographical narrative of three teachers at different moments of the training, pointed out and discussed the formative marks presented and what the impacts of this formation on the teacher who have chosen it. Four formative marks were defined - Responsibility in the formation of other human beings, critical thinking about the traditional pedagogical processes, admiration for the individual character of the Waldorf pedagogy and search for several forms of spirituality and, or, by the Anthroposophical Spiritual Science. This study showed the focus of the Waldorf formation on the individualities of each teacher that aims to enable them in the act of showing their students their unique characteristics.